Increase of efficiency of operation of transport vehicles in the conditions of low negative temperatures - L. N. Tyshkevich; B. V. Zhuravsky (Вестник СибАДИ, 2017)
The article considers the problem associated with the difficulty of start of refrigeration automobile internal combustion engine at low negative temperatures. This problem is particularly acute for the Russian Federation, as most of the territory of our country to be in a cold climate zone. The factors that affect the start of the diesel engine. It is shown that to improve the start-up and operating internal combustion characteristics at low negative temperatures is most effective display of their basic functional systems. It is said that in case of use as an energy source for electrical heating elements onboard battery is necessary to optimize the energy distribution. Powered device description and principles of the proposed automated system integrated thermal pre-start preparation diesel engines.